Web-based reading support system: assigning pronunciations to difficult words according to the vocabulary level of individual users. (2015) - Mizobuchi, Shoji; Ando, Kazuaki
This paper proposes a system that helps a user read a document on the web more easily by assigning pronunciations of difficult words in the document based on the vocabulary level of the user and the difficulties of characters in the document. Vocabulary level of a user and the difficulties of characters were estimated using the Item Response Theory (IRT). A simulation was conducted to evaluate the estimation of user vocabulary level. The results confirmed that the user vocabulary level can be estimated reasonably accurately when the user operates the pronunciations of half of the words with difficulties that are higher than his/her vocabulary level. The performance of the system was measured in terms of time and data size. The measurement results showed that the system performance was within an acceptable range.